2003
DOI: 10.1007/bf03040451
|View full text |Cite
|
Sign up to set email alerts
|

Die Chronisch Venöse Insuffizienz und ihr häufiges Vorkommen beim Krankenhauspersonal

Abstract: The study demonstrated that within a representative cross-section of hospital employees in a University hospital the prevalence of CVD was highest in women, especially in those working in a standing position or under conditions of high temperature and humidity. The results warrant regular evaluation of risk factors with subsequent primary prophylaxis of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
2
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 26 publications
6
56
2
5
Order By: Relevance
“…The strength of this study is that it provided cumulative incidence of VV risk among physicians and nonphysician HCP that was more specific than a previous study in Austria which reported that chronic venous diseases were present in a total of 70 general hospital employees (34%), predominantly among women [21] . However, that study included all chronic venous diseases and not only VV and it did not depict the individual results of physicians or comparisons with other populations [21] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The strength of this study is that it provided cumulative incidence of VV risk among physicians and nonphysician HCP that was more specific than a previous study in Austria which reported that chronic venous diseases were present in a total of 70 general hospital employees (34%), predominantly among women [21] . However, that study included all chronic venous diseases and not only VV and it did not depict the individual results of physicians or comparisons with other populations [21] .…”
Section: Discussionmentioning
confidence: 97%
“…However, that study included all chronic venous diseases and not only VV and it did not depict the individual results of physicians or comparisons with other populations [21] . Our study used the diagnosis made by physicians as the outcome measurement, which was also more objective than the questionnaire used in the abovementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Laurika et al found an increased prevalence of self-reported VV among Finnish 40, 50, and 60 year old men and women mainly standing at work (OR 1.6; 95% CI 1.4 to 1.8). 2 In a recent German study, Kroeger et al found that both a predominately sitting posture at work and a standing posture at work were associated with the prevalence of self-assessed and clinically diagnosed VV (OR = 2.2; 95% CI 1.2 to 3.9).…”
mentioning
confidence: 99%
“…Although their population was younger and leaner than the one described here, this mechanism could explain why less walking (more static postures) was associated with symptoms of OI among the participants in this study. The fact that chronic venous insufficiency has been found among hospital workers exposed to prolonged standing, particularly women, (Ziegler et al, 2003) suggest that the symptoms reported in this study may warn of circulatory problems to come.…”
Section: Symptoms Of Orthostatic Intolerancementioning
confidence: 78%
“…The results of the multiple regression show a significant effect of being female in addition to the effect of static standing. Several studies report that OI (Fu et al, 2004;Shoemaker et al, 2001;White et al, 1996), headaches (Lyngberg et al, 2005) and chronic venous insufficiency (White and Ryjewski, 2005;Ziegler et al, 2003) are more common in women. Hypotheses involving hormonal effects on symptoms could be explored.…”
Section: Male-female Differencesmentioning
confidence: 97%